Answer:
f(-2) = -1
f(0) = -5
f(4) = -1
Step-by-step explanation:
The number inside of f( ) is telling you which equation to use to get the answer.
Example:
f(-2) since -2 is less than 0 you would use (x^2) - 5. So, ((-2)^2) - 5 = 4-5 = -1
f(0) since 0 is less than or equal to 0 you would use (x^2) - 5 again. So, ((0)^2) - 5 = 0-5 = -5
f(4) since 4 is grater than 3 you would use (2^(x-1)) - 9. So, (2^(4-1)) - 9 = -1
<u><em>The Graph, try to make it as straight as possible</em></u>
<u><em></em></u>
The answer is Strong Positive
Answer:
I think its AED19
Step-by-step explanation:
please give brainliest if correct
It’s 101 because 72 and -29 have a difference of 101